Distância caminhada de seis minutos como determinante de prognóstico em pacientes com hipertensão arterial pulmonar em uma amostra da população brasileira - Costa, Gabriela Oliveira Siqueira [UNIFESP] (2019)
Introduction: The distance covered in the six-minute walk test (6MWD) is associated with the severity of patients with pulmonary arterial hypertension (PAH), having been used in several clinical studies to evaluate the efficacy of new drugs. Cutoff values ​​for DC6M are widely used as a tool for assessing prognosis in patients with PAH, including in our country, but there are no studies with the Brazilian population. Objectives: To identify cut-off values ​​of DC6M in a sample of patients with PAH in the Brazilian population and to compare the cut-off values ​​of DC6M derived from a sample of patients with PAH in the Brazilian population with the cut-off values ​​of DC6M recommended by international guidelines. Methods: Retrospective cohort study, involving 104 patients diagnosed with PAH between 03/2003 - 06/2016, at the Pulmonary Circulation Diseases Sector (Pulmonology - UNIFESP). Results: The median follow-up time was 10.7 years [8.9 - 12.5], a minimum of 174 days and a maximum of 11.4 years. The overall survival was 96%, 89%, 80% and 73%, respectively at 1, 2, 3 and 5 years. One hundred and four consecutive patients with PAH were allocated to groups according to the DC6M, considering 50 meters as a clinically relevant difference from DC6M. Then, groups with similar survival were condensed and the following cutoff points were found: <250 meters, 250-400 meters and> 400 meters. Cox analyzes adjusted for age, sex and aetiology of PAH showed that DC6M <250 meters and> 400 meters were associated with higher and lower mortality risk for all causes. The model based on regional values ​​adjusted for sex, age at diagnosis and functional class obtained a C index of 0.69, while the model derived from the cutoff values ​​recommended by international guidelines obtained a concordance index of 0.57. Conclusion: Our findings suggest that geographical variations of 6MWD should be considered when assessing risk stratification in PAH.